Alphavirus-Based Vaccines - Lundstrom, Kenneth (MDPI, 2014)
Alphavirus vectors have demonstrated high levels of transient heterologous gene expression both in vitro and in vivo and, therefore, possess attractive features for vaccine development. The most commonly used delivery vectors are based on three single-stranded encapsulated alphaviruses, namely Semliki Forest virus, Sindbis virus and Venezuelan equine encephalitis virus. Alphavirus vectors have been applied as replication-deficient recombinant viral particles and, more recently, as replication-proficient particles. Moreover, in vitro transcribed RNA, as well as layered DNA vectors have been applied for immunization. A large number of highly immunogenic viral structural proteins expressed from alphavirus vectors have elicited strong neutralizing antibody responses in multispecies animal models. Furthermore, immunization studies have demonstrated robust protection against challenges with lethal doses of virus in rodents and primates. Similarly, vaccination with alphavirus vectors expressing tumor antigens resulted in prophylactic protection against challenges with tumor-inducing cancerous cells. As certain alphaviruses, such as Chikungunya virus, have been associated with epidemics in animals and humans, attention has also been paid to the development of vaccines against alphaviruses themselves. Recent progress in alphavirus vector development and vaccine technology has allowed conducting clinical trials in humans.